Assessment of coloured sticky traps for the monitoring of flea beetles (Phyllotreta spp.) (Coleoptera: Chrysomelidae) in radish crop - Benakashree, C; Shanthi, M; Murugan, M; Shanmugam, P S; Harish, S; Govindan, K (Plant Science Today, 2025)
Flea beetles (Phyllotreta spp.) are herbivores that feed on Brassica plants and pose a significant threat, leading to considerable economic losses. Considering the increasing infestation of flea beetles in radish-growing areas across India, this study evaluated the effectiveness of coloured sticky traps - yellow, blue and white - in monitoring adult flea beetle, Phyllotreta chotanica Duvivier, populations in a radish field. The population density of flea beetles and percent leaf infestation was assessed weekly during trap capture observations across the radish crop cycle, from sowing to harvest. Blue traps were the most effective, with a peak of 7.00 ± 2.92 beetles per week at 49 days after sowing (DAS) and a mean of 4.89 beetles/week. Yellow traps also performed well, peaking at 7.00 ± 1.69 at 56 DAS, with a mean of 4.53 beetles/week. White traps were the least effective, with a mean of 2.89 beetles/week. Our findings indicate that blue and yellow traps captured the highest number of adult flea beetles, consistent with prior research demonstrating a preference for blue and yellow traps in agricultural settings. This study supports blue and yellow sticky traps as one of the better-integrated pest management (IPM) tools to implement as a prophylactic method of pest control for flea beetles in radish cultivation.